S21. THE IMPACT OF PERSISTENT NEGATIVE SYMPTOMS ON FUNCTIONING AND DEFEATIST BELIEFS IN YOUTH AT CLINICAL HIGH RISK FOR PSYCHOSIS. (9th April 2019) - Devoe, Dan; Liu, Lu; Cadenhead, Kristen; Cannon, Tyrone; Cornblatt, Barbara; McGlashan, Thomas; Perkins, Diana; Seidman, Larry J; Tsuang, Ming; Walker, Elaine; Woods, Scott; Bearden, Carrie; et al.
Abstract: Background: Persistent negative symptoms (PNS) are defined as enduring moderate negative symptoms while controlling for principal sources of secondary negative symptoms. PNS symptoms have been associated with poor functional outcomes in schizophrenia. Furthermore, in schizophrenia negative symptoms and poor functioning have been reportedly associated with defeatist beliefs (e.g., "I always fail"). Youth at clinical high risk (CHR) for developing psychosis often demonstrate negative symptoms, poor functioning, and defeatist beliefs. The goal of this study was to determine if negative symptoms were associated with poor functioning and defeatist beliefs in a CHR longitudinal cohort. Methods: CHR (N=764) participants were recruited for the North American Prodrome Longitudinal Study (NAPLS 2) at 8-sites across North America. Negative symptoms were rated on the Scale of Prodromal Symptoms (SOPS) at baseline, 6, 12, 18, and 24 months. For this study negative symptoms were restricted to social anhedonia (N1), avolition (N2), and expression of emotion (N3) based on recommendations from the NIMH-MATRICS consensus statement on negative symptoms. PNS were defined as having one of these three negative symptoms scored ≥4 (i.e., moderately severe to extreme) for a period of one year. Depressive symptoms were assessed with the Calgary Depression Scale for Schizophrenia (CDSS). To assess defeatist beliefs the Brief Core Schema Scale (BCSS) was utilized as a proxy to evaluate negative self-beliefs (e.g., "I am worthless") and positive self-beliefs (e.g., "I am valuable"). Generalized linear mixed models for repeated measures were used to examine changes over time between and within groups to accommodate for missing data and account for intra-participant correlations. Results: Sixty-seven CHR individuals had PNS. Mixed-effect models demonstrated that the PNS group had significant global, social, and role functioning deficits at baseline, 6, 12, 18, and 24 months compared to CHR individuals without PNS (n=673). Moreover, functioning did not improve in the PNS group while functioning in the group without PNS significantly improved over time. There were no significant differences between the groups on depressive symptoms with the CDSS. The PNS group had significantly higher BCSS self-negative beliefs at 12 and 24 months compared to the group without PNS. Individuals without PNS had significantly higher positive self-beliefs (e.g., "I am valuable") at baseline, 6 months, 12 months and 24 months compared to the PNS group. Discussion: The results indicate that in the NAPLS cohort 10% of CHR individuals have PNS. Moreover, the PNS group demonstrated significant and persistent global, social, and role functioning deficits compared to those without PNS. The group without PNS had higher levels of positive beliefs (e.g., "I am successful"), which may indicate a protective factor against developing PNS.